RANCANG BANGUN APLIKASI PENJUALAN BERBASIS WEB PADA CV. DUTA MANDIRI - Aditya Nugroho; Sakti Alfindo Bihalalika; Nurjaya (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
The development of information and communication technology has had a significant impact on various industrial sectors, including trade and services. CV. Duta Mandiri, a goods and services procurement company, still uses a manual sales system which is less effective and efficient. Therefore, it is necessary to develop a web-based sales application that can increase operational efficiency and make it easier for customers to place orders. This study aims to analyze functional and non-functional requirements in developing webbased sales applications for CV. Independent Ambassador. Needs analysis includes identifying the company's operational problems, customer needs in placing orders, and selecting the right technology to meet these needs. The results of this study are expected to provide a solution for CV. Duta Mandiri in improving company performance and providing better service to customers. This web-based sales application allows customers to place orders online, anytime and anywhere, without the need for a direct visit to CV. Independent Ambassador. In addition, this application is expected to improve operational efficiency and reduce errors in managing business transaction data.